Do the National English journals provide clear research gaps? An analysis of published journals - -, Ashar Fauzi; Tiara Ayu Kusuma Dewi (EDULANGUE, 2024)
This study provides a critical review of the nationally published journals, especially in highlighting the research gaps. This focus of the study comes from our interest that there is a policy that obligates lecturers and students to publish a journal article in nationally or internationally indexed journal outlets. This puts so much pressure on them in the academic sector (Arsyad & Adila, 2017). The result of this study will help further researchers in writing their research gaps. We adopt document analysis (Hatch, 2002; Merriam & Tisdell, 2016) and theme-rheme analysis to reveal the structure of paragraphs and sentences in the introduction section, especially in deciding the research gap. We analyzed one English-published journal that is indexed in Sinta 1, Sinta 2, Sinta 3, Sinta 4, Sinta 5, and Sinta 6. Findings show that the journals mention the research gap in the introductory paragraph. However, the structural quality needs significant improvement. We suggest to the authors of the journals, editors, and further researchers or practitioners to have a good understanding of how to craft a good introductory paragraph and follow the ethics of doing research. We suggest that further research focus on providing insight into teaching writing for scholarly publication